Сорбция меди и никеля фосфорилированными сорбентами в статических условиях - Хохотва, Александр Петрович; Маслянка, Карина Сергеевна (НТУ "ХПИ", 2019)
Использование древесных отходов лесной промышленности в качестве источника сырья для производства дешевых углеродистых адсорбентов является перспективной стратегией, которая может помочь решить и проблему утилизации отходов. Известно, что наличие поверхностных функциональных групп усиливает способность углеродных сорбентов адсорбировать ионы металлов из водных растворов. Модификация углеродных сорбентов соединениями фосфора приводит к появлению кислотных свойств и повышению сорбционных свойств по отношению к тяжелых металлов. Из сосновых опилок путем термохимической обработки при 170 °С с предварительной пропиткой растворами активатора карбонизации ортофосфата аммония различных концентраций в присутствии карбамида и без него получен ряд фосфорилированных сорбентов и исследованы их сорбционные свойства по отношению к ионам никеля и меди.

Pollution by heavy metal ions are one of the main anthropogenic threat to the nature as they do not decay, are stable in the environment and can accumulate along food chains. Not-sufficiently treated industrial waste waters are the primary source of such pollution. Application of wood waste from forestry industry as a source of raw material for production of cheap carbonaceous adsorbents is a promising strategy, which can help to solve also the waste utilization problem. It is known that the presence of surface functional groups enforces the capability of carbon sorbents to adsorb metal ions from aqueous solutions. The modification of carbon sorbents with phosphorus compounds leads to the creation of acidic properties and increase of sorption properties to heavy metals. Heteroatoms of phosphorus can be introduced into the carbon structure by modification of hydrocarbon raw material both before carbonization and into ready carbon adsorbent. A series of phosphorylated sorbents was obtained from pine sawdust by thermochemical treatment at 170 °C with preliminary impregnation by ammonium orthophosphate (carbonization activator) solutions of various concentrations in the presence of urea and without it. Their sorption properties with respect to nickel and copper ions were studied. The lowest residual concentrations of metals at the level of few mg/l were achieved using sorbents obtained by phosphorylation in the presence of urea with a relatively short duration of heat treatment.
Sorption of copper and nickel by phosphorylated sorbents in static conditions
Keywords: сосновые опилки; фосфат аммония; карбамид; адсорбция; карбонизация; pine sawdust; ammonium phosphate; urea